2007
DOI: 10.1099/ijs.0.64344-0
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence analysis of Ensifer and related taxa

Abstract: Multilocus sequence analysis (MLSA) was performed on representatives of Ensifer (including species previously assigned to the genus Sinorhizobium) and related taxa. Neighbour-joining (NJ), maximum-parsimony (MP) and maximum-likelihood (ML) phylogenies of dnaK, gltA, glnA, recA, thrC and 16S rRNA genes were compared. The data confirm that the potential for discrimination of Ensifer species is greater using MLSA of housekeeping genes than 16S rRNA genes. In incongruence-length difference tests, the 16S rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(125 citation statements)
references
References 78 publications
5
112
0
8
Order By: Relevance
“…The relative divergence of the reference strain WSM 419 from the population Population genomics of Sinorhizobium medicae X Bailly et al we sampled was greatest for the chromosome and least for pSMED1 and pSMED2, as estimated by the K ST statistic (Table 4). The low genetic divergence on the chromosome between S. medicae WSM 419 and the population we sampled (0.0029 substitutions per bp), compared with the genetic divergence of around 0.1 substitutions per bp described between S. medicae and S. meliloti isolates based on multilocus sequence typing data (Bailly et al, 2006;van Berkum et al, 2006;Martens et al, 2007), confirms our initial assumption that our isolates were all S. medicae. We investigated the degree to which the phylogenetic signal was consistent across the genome by means of a PCA.…”
Section: Genetic Divergence For Genome Regions Shared With Wsm 419supporting
confidence: 78%
See 1 more Smart Citation
“…The relative divergence of the reference strain WSM 419 from the population Population genomics of Sinorhizobium medicae X Bailly et al we sampled was greatest for the chromosome and least for pSMED1 and pSMED2, as estimated by the K ST statistic (Table 4). The low genetic divergence on the chromosome between S. medicae WSM 419 and the population we sampled (0.0029 substitutions per bp), compared with the genetic divergence of around 0.1 substitutions per bp described between S. medicae and S. meliloti isolates based on multilocus sequence typing data (Bailly et al, 2006;van Berkum et al, 2006;Martens et al, 2007), confirms our initial assumption that our isolates were all S. medicae. We investigated the degree to which the phylogenetic signal was consistent across the genome by means of a PCA.…”
Section: Genetic Divergence For Genome Regions Shared With Wsm 419supporting
confidence: 78%
“…meliloti and S. medicae are closely related species that form a tight phylogenetic clade together with Sinorhizobium arboris (Martens et al, 2007). The genomes of S. meliloti 1021 and S. medicae WSM 419 share similar architectures.…”
Section: Introductionmentioning
confidence: 99%
“…meliloti (1,14,31,54). Moreover, phylogenies based on a sample of housekeeping genes suggest that S. meliloti and S. medicae are not sister species (28). Most of the topologies obtained indeed suggest that S. medicae might be the first emerging taxon within a clade including S. medicae and S. meliloti but also another species, Sinorhizobium arboris (28), suggesting a rather ancient speciation event leading to the first two species.…”
Section: Discussionmentioning
confidence: 99%
“…MLSA-based phylogenetic analyses were preformed by studying sequence information on the housekeeping genes that encode ATP synthase beta subunit (atpD), heat-shock protein Hsp70 (dnaK), glutamine synthetase II (glnII), DNA gyrase subunit B (gyrB), and recombinase A protein (recA) as well as on 16S rRNA genes and the ITS region. PCR amplifi cations of atpD, dnaK, glnII, gyrB, and recA genes were performed using specifi c primer sets of atpD255F/ atpD782R, dnaK1466F/dnaK1777R, glnII12f/glnII689r, gyrB343F/gyrB1043R, and recA41F/recA649R, respectively, under optimized PCR conditions as reported (Martens et al, 2007(Martens et al, , 2008Vinuesa et al, 2005). The ITS sequences were amplifi ed with a primer set of 1492f (Lane, 1991) and LS117r (Okamura et al, 2009) as described.…”
Section: Analysis Of Ahdo Genes and Reverse-transcription Pcrmentioning
confidence: 99%
“…These levels of similarity correspond to the threshold of grouping bacterial strains as a genetically single species (Stackebrandt and Ebers, 2006). To get a more comprehensive understanding of the taxonomic position of our isolates, therefore, we performed the MLSA of housekeeping genes and the ITS region, which has been successfully made for phylogenetic studies on Rhizobium species and related alphaproteobacteria (Martens et al, 2007;Menna et al, 2009;Okamura et al, 2009;Tan et al, 2001;Willems et al, 2001). In this study, the MLSA analysis of the atpD, dnaK, gluII, gyrB, and recA genes and the ITS region has revealed that our isolates represent a distinct lineage within the genus Rhizobium with R. selenitireducens as their phylogenetic neighbor.…”
Section: Taxonomic Considerationmentioning
confidence: 99%